Epidemiology of group B streptococcal infection in pregnant women and diseased infants in mainland China - Jing Huang; Xin-Zhu Lin; Yao Zhu; Chao Chen (Elsevier, 2019)
Group B Streptococcus (GBS) is a leading cause of neonatal sepsis and an important cause of maternal disease in many countries; however, no accurate population-based epidemiological data on GBS is yet available in mainland China. In this systematic literature review, we obtained published data regarding the maternal GBS colonization rate, incidence of invasive GBS disease in infants, clinical screening, and the associated GBS typing and clinical outcomes in China. The maternal GBS colonization rate in mainland China ranged from 3.7 to 14.52%, and the incidence of invasive GBS disease in infants was 0.55-1.79 per 1000 live births, with a case fatality risk ranging from 6.45 to 7.1%. Serotype III was the dominant serotype that was observed in GBS isolates. GBS detection and identification has become more commonplace, due to the availability of polymerase chain reaction and DNA microarray technologies. Immunizing pregnant women against GBS is an emerging approach through which newborns are protected from GBS. The available data suggest that five GBS serotypes (Ia, Ib, II, III, and V) account for the majority of the cases of GBS disease in mainland China. Furthermore, conjugate vaccines comprising some or all of these serotypes are of potential value in the prevention of GBS infection. Key Words: colonization, group B streptococcus, neonatal infection, serotype distribution, sequence type